Introduction - Anselm J Hennis; Mauricio Hernández-Ávila (Instituto Nacional de Salud Pública, 2017)
This special supplement for Salud Pública de México: "Tobacco Control in the Americas: from Evidence to Public Policy" is part of the ongoing collaboration of the Pan American Health Organization/World Health Organization (PAHO/WHO) and the Centers for Disease Control and Prevention (CDC) to support the countries of the Americas in the area of tobacco control surveillance and monitoring in compliance with Article 20 of the WHO Framework Convention on Tobacco Control (WHO FCTC).